Computer forensics jumpstart - Solomon, Michael [ (Michael G.)] , 1963-; Barrett, Diane; Broom, Neil; Rudolph, K.; Tittel, Ed (Wiley, 2011)
A guide to computer forensics provides information on such topics as conducting a forensics investigation, finding hidden data, capturing images, collecting and preserving computer evidence, and using computer forensic tools